1999
DOI: 10.1007/bf02345583
|View full text |Cite
|
Sign up to set email alerts
|

Production of carrier free192,193Hg and192,193Au in16O irradiated tantalum target and their separation by liquid-liquid extraction

Abstract: Carrier-free radionuclides of mercury and gold 192,193Hg and 192,193Au have been produced by heavy ion activation of tantalum target with 95 MeV 1605 § beam obtained from an ECR ion source. An effective radiochemical separation scheme has been developed to isolate gold and mercury radionuclides from the tantalum target matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Several authors reported 193 Au as a potential radioactive tracer in materials science and biophysics research [17,18]. On the other hand, Lahiri et al [19] proposed the replacement of conventionally used radiogold nuclides 195 Au and 199 Au by the short-lived 192 Au and 193 Au in medical applications.…”
Section: Introductionmentioning
confidence: 98%
“…Several authors reported 193 Au as a potential radioactive tracer in materials science and biophysics research [17,18]. On the other hand, Lahiri et al [19] proposed the replacement of conventionally used radiogold nuclides 195 Au and 199 Au by the short-lived 192 Au and 193 Au in medical applications.…”
Section: Introductionmentioning
confidence: 98%
“…For example, in the context of gold radionuclide production, our laboratory reported production of 192,193 Au as daughter product of 192,193 Hg which was produced by irradiating tantalum target with 95 MeV 16 O beam. However, they did not measure the corresponding excitation function [8]. In the present work, an attempt has been made to systematically measure the production cross section of nat W( 11 B,xn) reaction upto 63 MeV projectile energy and investigate an alternate production route of the [190][191][192][193] Au radionuclides.…”
Section: Introductionmentioning
confidence: 99%
“…Previously we have reported separation of no-carrier-added radioisotope of gold produced in neutron activated platinum target [11,12]. No-carrieradded radioisotopes of mercury and gold were produced by 16 O 7ϩ irradiation on tantalum target and subsequent separations were also carried out [13].…”
Section: Introductionmentioning
confidence: 99%